2019
DOI: 10.1111/fmii.12115
|View full text |Cite
|
Sign up to set email alerts
|

Motivating high‐impact innovation: Evidence from managerial compensation contracts

Abstract: We investigate the relationship between Chief Executive Officer (CEO) compensation and firm innovation and find that long‐term incentives in the form of options, especially unvested options, and protection from managerial termination in the form of golden parachutes are positively related to corporate innovation, and particularly to high‐impact, exploratory (new knowledge creation) invention. Conversely, non‐equity pay has a detrimental effect on the input, output and impact of innovation. Tests using the pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 108 publications
(201 reference statements)
0
9
0
Order By: Relevance
“…Positive momentums in R&D innovations that extend from previous successes through CEOs' change seem unaffected by CEO compensation (Tien and Chen, 2012). However, contrary to this, when considering non-equity pay, studies find that it has a detrimental effect on innovation (Francis et al , 2019). Even though compensations protect the CEOs from projects' failures in their early stages and incentivizes more long-term commitments like unvested options, together with golden parachutes, such compensations induce corporate innovation (Francis et al , 2019).…”
Section: Contradictions In the Past Research Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Positive momentums in R&D innovations that extend from previous successes through CEOs' change seem unaffected by CEO compensation (Tien and Chen, 2012). However, contrary to this, when considering non-equity pay, studies find that it has a detrimental effect on innovation (Francis et al , 2019). Even though compensations protect the CEOs from projects' failures in their early stages and incentivizes more long-term commitments like unvested options, together with golden parachutes, such compensations induce corporate innovation (Francis et al , 2019).…”
Section: Contradictions In the Past Research Literaturementioning
confidence: 98%
“…However, firms use multiple performance measures in contracts with CEOs. Among these, the percentage of stock return is a price–performance measure, which can reduce CEOs' risk-taking behavior to shield the CEOs from value-enhancing project selections (Duru et al , 2002) and early failures (Francis et al , 2019).…”
Section: Contradictions In the Past Research Literaturementioning
confidence: 99%
“…However, prior studies have not reached a consensus on whether vesting periods can induce innovation. Some researchers believe that long-term compensation contracts, combined with golden parachutes and other interest-related protection measures for top executives, are more effective in stimulating R&D expenditure and innovation output [ 13 , 14 ]. In contrast, others find that implementing long-term incentives is a double-edged sword [ 24 , 29 ].…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Prior studies have found that equity incentive have a positive effect on corporate innovation [ 4 , 12 ]. And incentive schemes with long vesting periods lead to better innovation performance [ 13 , 14 ]. Current literature usually uses R&D investment and patent output to measure innovation, but these measures have significant limitations in measuring innovation [ 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, funding policies that tolerate early failure and reward long-term success motivate innovation in scientific research [ 29 ]. A positive relationship between innovation and compensation schemes which protect managers from termination is also documented [ 30 ]. Also, innovation is documented to be greater when the bankruptcy code is debtor-friendly [ 31 ].…”
Section: Introductionmentioning
confidence: 99%